Analysis of Community Saving Interest in Bank Mega Syariah through Islamic Banking Literacy and Family Environment with Trust in Islamic Banking as an Intervening Variable - Ferdiana Dwi Analia; Titing Widyastuti (Yayasan Amerta Insan Unggul, 2024)
Islamic banks provide financing that complies with Sharia principles and do not impose interest payments, as only goods or services are allowed to bear prices. Speculation is not permitted, and funding for illegal activities is prohibited. This study aims to examine the influence of Sharia financial literacy and family environment on public interest in saving at Islamic banks through trust in Islamic banks. The research method employed is quantitative. The data analysis technique used in this study is path analysis. The population consists of individuals who are customers of Islamic banks in Depok. Sampling was conducted using purposive sampling, with a total of 84 respondents. Data collection was carried out through questionnaires. From the results of the research, the limited results of proving the theory of the relationship between the variables Sharia Banking Literacy, family environment on people's interest in saving in Bank Syariah (Y) and also trust in sharia banking are interesting findings, the results of the independent and intervening variables are positive and significant and also have an effect. Directly or indirectly, this can happen because the results of data processing fully reflect the existing reality. The research results prove that literacy in sharia banking and the family environment, mediated by public trust in sharia banking, can create significant results in people's interest in saving. The potential of Indonesian society, which is 80% Muslim, is the strength of Bank Mega Syariah to get closer to society.